HUBUNGAN AKTIVITAS FISIK DENGAN DAYA TAHAN KARDIOVASSKULAR PADA ANGGOTA PERSATUAN ATLETIK MASTER INDONESIA (PAMI) KOTA MALANG - Rio Hidayanto Pratama; Hartati Eko Wardani; Laras Putri Gamagitta; Supriyadi; Moch Yunus (Jayabama: Jurnal Peminat Olahraga, 2024)
Persatuan Atlet Master Indonesia (PAMI) Malang City is an elderly sports community that has a fairly high training intensity, namely 4-5 times per week. However, there are several members who have cardiovascular endurance below the average of other PAMI colleagues. This is because their physical activity is low and they often do not attend training, resulting in fatigue when doing heavy activities which will cause sprains, fainting, hypothermia and shortness of breath (dyspnea). This study aims to determine the relationship between physical activity and cardiovascular endurance in PAMI athletes in Malang City. This research is quantitative with a cross-sectional approach with a population of all PAMI Malang City athletes registered in 2023. The sample used was 30 athletes taken using a purposive sampling technique who had passed the inclusion and exclusion criteria. Data collection was carried out by filling out the Global Physical Activity Questionnaire (GPAQ) and Multistage Fitness Test (MFT) questionnaires. The results of the Spearman rank test showed that (r=0.932; p=0.000*) there was a significant relationship between physical activity and cardiovascular endurance in PAMI Malang City.